NECROTIZING FASCIITIS OF THE RIGHT FLANK MIMICKING A XANTHOGRANULOMATOUS PYELONEPHRITIS (Indonesian Urological Association, 2022)
Objective: Xanthogranulomatous pyelonephritis (XGP) is a rare and serious chronic inflammation of the kidney, manifesting as a granulomatous inflammation of the kidney tissue. It can be life-threatening if not recognized and managed appropriately with antibiotics and surgery. Since there are no single pathognomonic clinical or radiological features, diagnosis requires combining the results of several clinical signs and imaging characteristics. However, determining the disease is oftentimes difficult as other conditions may mimic its characteristics, such as renal cancer, mesoblastic nephroma, renal abscess, and necrotizing fasciitis. Case(s) Presentation: A 45-year-old man was admitted to the emergency department of Soetomo General-Academic Hospital with right flank gangrene and fever for one week. Discussion: The patient was admitted to the hospital with sepsis and poor laboratory result. Computed Tomography (CT) scan results showed nephrolithiasis. The patient was diagnosed with Xanthogranulomatous pyelonephritis and underwent necrotomy in the Emergency Operating theatre. Conclusion: During the operation, necrotizing fasciitis was found in the right flank region instead. The external oblique muscle was intact without any tunneling into the retroperitoneal space. The postoperative care was joined by the Plastic Surgery department.